Unified functional method for solving general polynomial equations of degree less than five / Dozie Felix Nwosu ...[et al.] - Nwosu, Dozie Felix; Okoli, Odilichukwu Christian; Ezeonyebuchi, Amaka; Tiruneh, Ababu Teklemariam (Penerbitan UiTM, 2021)
A unified method for solving general polynomial equation of degree less than five that incorporate a computational formula that relate the coefficients of the depressed equation and the coefficient of the standard polynomial equation is proposed in this study. This is to ensure that this method is valid for all degree less than five. It shall apply the undetermined parameter method of auxiliary function to obtain solutions to these polynomial equations of degree less than five in one variable. In particular, the result of our work is a unification and improvement on the work of several authors in the sense that only applicable for the case of polynomial equation of degree one. Finally, our results improve and generalize the result by applying standard formula methods for solving higher degree polynomials. It is recommended that the effort should be made toward providing other variant methods that are simpler and friendly.